2016
DOI: 10.1136/bmjopen-2016-011887
|View full text |Cite
|
Sign up to set email alerts
|

Parents' and carers' views about emollients for childhood eczema: qualitative interview study

Abstract: ObjectiveLeave-on emollients form the mainstay of eczema treatment, but adherence is poor. We aimed to explore parents’/carers' views on effectiveness and acceptability of leave-on emollients for childhood eczema through secondary analysis of data from 2 qualitative data sets.SettingStudy 1 recruited through mail-out from 6 general practices in southern England. Study 2 recruited from a feasibility trial of an intervention to support eczema self-care in 31 practices in the same area.ParticipantsStudy 1 include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“… 5 This was reflected in our interviews with parents where they persisted with topical therapy but often felt it was ineffective. Santer et al 29 found that parents had mixed views about long-term use of emollients to prevent flare-ups and this was echoed by the GPs in our study who said that parents were not using emollients for long enough to be effective and were expecting results with short-term use. Education about the rationale for emollients may lead to more positive parental attitudes towards long-term use.…”
Section: Discussionmentioning
confidence: 54%
“… 5 This was reflected in our interviews with parents where they persisted with topical therapy but often felt it was ineffective. Santer et al 29 found that parents had mixed views about long-term use of emollients to prevent flare-ups and this was echoed by the GPs in our study who said that parents were not using emollients for long enough to be effective and were expecting results with short-term use. Education about the rationale for emollients may lead to more positive parental attitudes towards long-term use.…”
Section: Discussionmentioning
confidence: 54%
“…Nevertheless, children living with AD remain an underrepresented group attracting little social or academic attention. Previous qualitative studies have preferred to focus on the perceptions or experiences of issues related to AD management among the parents and caregivers of children living with AD (Halls et al, ; Santer et al, , ; Teasdale, Muller, & Santer, ). The current qualitative study contributes to amplifying the voices of children living with AD by providing a contextualised description of their subjective experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that parents have misconceptions about treatment of pediatric AD symptoms and encounter difficulties with the proper application of topical medication [ 13 – 15 ]. Inconsistent information between dermatologists, general practitioners (GPs) and pharmacists on the risks and benefits of TCS and proper use of emollients may cause confusion among patients and could negatively affect appropriate use of treatment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%